2017
DOI: 10.1093/femsle/fnx075
|View full text |Cite
|
Sign up to set email alerts
|

Inulin with different degrees of polymerization modulates composition of intestinal microbiota in mice

Abstract: The study aimed to analyze the global influences of dietary inulin with different degrees of polymerization (DP) on intestinal microbial communities. Six-week-old male C57BL/6J mice were treated with fructo-oligosaccharides and inulin for 6 weeks. Fecal samples were obtained at time point 0 and 6th week. 16S rRNA sequence analysis was used to measure intestinal microbiota performed on the Illumina MiSeq platform. Influences of dietary inulin on intestinal microbiota were more complex effects than bifidogenic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 31 publications
10
36
2
2
Order By: Relevance
“…Among these bacteria, we found that the relative abundance of A. muciniphila increased more than 100-fold following the ingestion of prebiotics thereby reaching the abundance of up to 4.5% under high-fat diet ( Everard et al, 2014 ), whereas this effect was lower under normal chow diet (0.09–2.5%) depending on the model ( Everard et al, 2011 , 2014 ). It is worth noting that these findings are confirmed in different set of experiments ( Everard et al, 2013 ; Liu et al, 2016 ; Reid et al, 2016 ; Catry et al, 2017 ; Zhu et al, 2017 ). Interestingly, we and others discovered that A. muciniphila was less abundant in the intestinal microbiota of both genetic and diet-induced obese and diabetic mice ( Everard et al, 2011 , 2013 , 2014 ; Schneeberger et al, 2015 ; Leal-Diaz et al, 2016 ; Ojo et al, 2016 ; Song et al, 2016 ; Singh et al, 2017 ), however, few studies reported in mice an increased abundance of A. muciniphila upon the ingestion of a high-fat high sucrose diet ( Anhe et al, 2015 ; Carmody et al, 2015 ).…”
Section: From Prebiotic To Next-generation Beneficial Microbe: Focus supporting
confidence: 67%
“…Among these bacteria, we found that the relative abundance of A. muciniphila increased more than 100-fold following the ingestion of prebiotics thereby reaching the abundance of up to 4.5% under high-fat diet ( Everard et al, 2014 ), whereas this effect was lower under normal chow diet (0.09–2.5%) depending on the model ( Everard et al, 2011 , 2014 ). It is worth noting that these findings are confirmed in different set of experiments ( Everard et al, 2013 ; Liu et al, 2016 ; Reid et al, 2016 ; Catry et al, 2017 ; Zhu et al, 2017 ). Interestingly, we and others discovered that A. muciniphila was less abundant in the intestinal microbiota of both genetic and diet-induced obese and diabetic mice ( Everard et al, 2011 , 2013 , 2014 ; Schneeberger et al, 2015 ; Leal-Diaz et al, 2016 ; Ojo et al, 2016 ; Song et al, 2016 ; Singh et al, 2017 ), however, few studies reported in mice an increased abundance of A. muciniphila upon the ingestion of a high-fat high sucrose diet ( Anhe et al, 2015 ; Carmody et al, 2015 ).…”
Section: From Prebiotic To Next-generation Beneficial Microbe: Focus supporting
confidence: 67%
“…Muribaculaceae is a newly proposed family encompassing OTUs previously classified as Porphyromonadaceae in some databases 36 . The abundance of Muribaculaceae, for which the name family S24-7 was previously used, was reported to be increased by inulins in our previous study 37 , and this family was versatile with respect to complex carbohydrate degradation 36 . This result indicated that LC inulin was more dependent on bacteria capable of processing complex polysaccharides than SC inulin because any fermentable carbohydrates, especially highly polymerized inulin, must be hydrolyzed to simple sugars before utilization by bacteria.…”
Section: Discussionmentioning
confidence: 82%
“…Also, different polymerization degrees of dietary polysaccharides have moderately different effects on intestinal microbiota. As in a report, the low degree of polymerized inulin performed better on modulating the intestinal microbiota than the high degree of polymerized inulin did in vivo [ 25 ]. All these results reveal that the glycosidic linkage type determines the effects of the polysaccharides on the structure, diversity and metabolism of gut microbiota.…”
Section: Influences Of Natural Polysaccharides On Intestinal Micromentioning
confidence: 78%